Queer-Feminist Punk - Wiedlack, Katharina (2015)
This history makes use of anti-social theory to take a broad and multifaceted look at queer-feminist punk—from its origins in the 1980s to its contemporary influences on the Occupy movement and Pussy Riot activism.